Serum neurofilament light chain: No clear relation to cognition and neuropsychiatric symptoms in stable MS. Issue 6 (November 2020) - Aktas, Orhan; Renner, Alina; Huss, André; Filser, Melanie; Baetge, Sharon; Stute, Nathalie; Gasis, Marcia; Lepka, Klaudia; Goebels, Norbert; Senel, Makbule; Graf, Jonas; Enzinger, Christian; et al.
Abstract : Objective: To explore the hypothesis that serum neurofilament light chain (sNfL) indicative of neuroaxonal damage may improve precise disease profiling with regard to cognition and neuropsychiatric symptoms, we analyzed potential associations of sNfL levels with cognitive test scores, fatigue, depression, and anxiety. Methods: Patients with relapsing-remitting and secondary progressive MS (SPMS) underwent an elaborated assessment including MRI, various cognitive tests, and patient-reported outcomes. We determined sNfL levels by single molecule array (Simoa) assay. Relationships between sNfL, cognition, neuropsychiatric symptoms, and demographical data were analyzed using correlations, group comparisons, and regressions. Results: In 45 clinically stable patients with MS (Expanded Disability Status Scale = 2.73 ± 1.12, disease duration = 10.03 ± 7.49 years), 40.0% were cognitively impaired. Mean sNfL levels were 16.02 ± 10.39 pg/mL, with higher levels in the SPMS subgroup ( p = 0.038). sNfL levels did reliably link neither with the investigated cognitive and affective parameters nor with fatigue levels. The only relationship found in a small subgroup of patients with SPMS (n = 7) with visuospatial learning ( r = −0.950, p = 0.001) and memory ( r = −0.813; p = 0.026) disappeared when further controlling for age, educational level, and sex. Conclusions: In patients with stable MS at less advanced disease stages, sNfL did not convincingly relate to cognitive performance, fatigue, depression, or anxiety and thus may not serve as a surrogate biomarker for neuropsychological status in such populations.